Protótipo para monitoramento dos parâmetros de temperatura em módulos fotovoltaicos por Internet das Coisas - IoT - Rodrigues, João (2021)
This course conclusion work was committed to evaluating the availability of applying a prototype that would enable the user to monitor, in real time, the temperature parameters of a photovoltaic system, considering the impact that temperature variations have in the production of energy from photovoltaic generators. The objective of the study was to understand the possibility of developing this prototype using the Wi-Fi Module NodeMCU ESP8266 ESP-12E, capable of implementing in any system, the possibility of connecting to the Internet through Wi-Fi. The prototype assists in the process of obtaining system temperature data and also enables the implementation of various sensors and actuators, in addition to complex and automatic programs and functions, enabling the prototype user to make intelligent decisions based on their own statistical data of the generator system, since the analysis of the measured results is done in a simple way through the AllThingsTalk Maker application server. Improving the efficiency of these processes through their intelligent automation, using intelligent sensors and Arduino's free programming. So, different tests were carried out, one involving computer simulation of the prototype and the characteristics of a photovoltaic module, and the other that was done through the physical construction of the prototype and measurements carried out at room temperature and in a cup of hot water. It was clear that the prototype was successful in carrying out temperature measurements and making these results available for analysis by the user, which can be accessed over the Internet. It was not possible to develop the measurements on a real photovoltaic module, given the extreme situation in Brazil.